Union Density, Productivity and Wages - Erling Barth; Alex Bryson; Harald Dale-Olsen (Institute of Labor Economics (IZA), 2017)
We exploit tax-induced exogenous variance in the price of union membership to identify the effects of changes in firm union density on firm productivity and wages in the population of Norwegian firms over the period 2001 to 2012. Increases in union density lead to substantial increases in firm productivity and wages having accounted for the potential endogeneity of unionization. The wage effect is larger in more productive firms, consistent with rent-sharing models.
Keywords: J01; J08; J50; J51; 330; trade unions; union density; productivity; wages